HIGH ENERGY PHYSICS EXPERIMENTS IN GRID COMPUTING NETWORKS - Olszewski, Andrzej (Computer Science, 2013)
The demand for computing resources used for detector simulations and data analysis in HighEnergy Physics (HEP) experiments is constantly increasing due to the development of studiesof rare physics processes in particle interactions. The latest generation of experiments at thenewly built LHC accelerator at CERN in Geneva is planning to use computing networks fortheir data processing needs. A Worldwide LHC Computing Grid (WLCG) organization hasbeen created to develop a Grid with properties matching the needs of these experiments. Inthis paper we present the use of Grid computing by HEP experiments and describe activitiesat the participating computing centers with the case of Academic Computing Center, ACKCyfronet AGH, Kraków, Poland.